Ecological study on child nutrition in Indonesia: National urban–rural patterns and local-level variation - Intan Qanita; Nuril F. Abshori; Derren DCH. Rampengan; Roy Ramadhan; Arga S. Adji; Fahrul Nurkolis; Hatem B. Al-Abdullah; Sami A. Al-Dubai (Narra X, 2025)
Indonesia continues to face a double burden of malnutrition, characterized by persistent undernutrition and a growing prevalence of overweight among children. Although urban children typically show lower rates of stunting and underweight, emerging evidence indicates rising obesity due to unhealthy behavior. At the same time, national indicators may mask substantial heterogeneity at the provincial and district levels. This study aimed to compare urban–rural disparities in child nutrition and maternal care at the national level and examines intra-provincial variation that may be obscured by aggregated statistics. An ecological analysis was conducted using data from the 2024 Indonesian Nutritional Status Survey. Urban–rural differences were evaluated using odds ratios (OR) and Chi-square tests. Sub-provincial analyses were undertaken in selected districts of Central Java and South Sulawesi to assess patterns of variation across smaller administrative units. At the national level, urban children exhibited lower odds of severe underweight (OR: 0.78; 95%CI: 0.75–0.81), underweight (OR: 0.82; 95%CI: 0.80–0.84), and stunting (OR: 0.77; 95%CI: 0.75–0.78). In contrast, they had higher odds of being at risk of overweight (OR: 1.35; 95%CI: 1.31–1.40) and of consuming unhealthy foods (OR: 1.22; 95%CI: 1.19–1.25). Rural areas showed poorer dietary diversity and lower coverage of antenatal care. District-level analyses revealed marked contrasts, where in Central Java, Magelang Municipality had lower odds of severe underweight than Surakarta and Tegal Municipalities. Meanwhile, in South Sulawesi, Makassar Municipality performed better than Pare-pare Municipality but still lagged behind Tana Toraja. These intra-provincial patterns suggest that urban residence does not uniformly confer nutritional advantage. Significant inequities persist not only between urban and rural populations but also across districts within the same province. Smaller cities with stronger health service access, such as Magelang Municipality, tend to show better child nutrition outcomes.